THE POLITICAL OF PESANTREN IN THE 2018 EAST JAVA GOVERNOR ELECTION ON MADURA ISLAND - Anshori, Ahmad Bahrul; Samputra, Palupi Lindiasari (Universitas Padjadjaran, 2024)
Pesantren and East Java (Jatim) share a mutualistic, symbiotic relationship in political and cultural spheres. Pesantren is a byproduct of East Javan culture and a voting platform for regional elections. This study aims to ascertain the elements that voters on Madura Island consider when selecting a candidate in the 2018 East Java Governor Election. A mixed method comprising qualitative and quantitative elements and logistic regression data analysis techniques was employed to accomplish these research aims. According to the study’s findings, voters consider four elements: job programs, political parties, pesantren politics, and support from the contemporary Muslim community. Concurrently, these four elements impact the Khofifah-Emil candidate team’s outcome. According to the logistic regression findings, the Khofifah-Emil candidate team’s pesantren political strategy is to increase the number of graduate networks and pesantren support